Пошаговое объяснение:
№1
(-0,5в⁶)³ * 5в = (-0,5)³ * (в⁶)³ * 5в =
-0,125 * в¹⁸ * 5в = (-0,125 * 5) * (в¹⁸ * в) =
-0,625 * в¹⁹ = -0,625в¹⁹
№2
3у + (у - 2) = 2(2у - 1)
3у + у - 2 = 4у - 2
4у - 2 = 4у - 2
Утверждение верно для любого значения у, так как обе части одинаковые
у Є R
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Пошаговое объяснение:
№1
(-0,5в⁶)³ * 5в = (-0,5)³ * (в⁶)³ * 5в =
-0,125 * в¹⁸ * 5в = (-0,125 * 5) * (в¹⁸ * в) =
-0,625 * в¹⁹ = -0,625в¹⁹
№2
3у + (у - 2) = 2(2у - 1)
3у + у - 2 = 4у - 2
4у - 2 = 4у - 2
Утверждение верно для любого значения у, так как обе части одинаковые
у Є R